PENERAPAN AJARAN SUSILA PADA LINGKUNGAN KELUARGA HINDU DI PERUMAHAN BTN BELEGA KECAMATAN BLAHBATUH KABUPATEN GIANYAR - I Made Suparma Netra I Made Suparma Netra; Relin D.E.; I Made Arsa Wiguna (Jurnal Pendidikan Agama, 2023)
Applying moral teachings in the lives of Hindus, particularly in shaping the character and behavior of children, is of utmost importance. This process can begin within the Hindu family environment to foster harmonious relationships in society, with the aim of raising children who become positive contributors to their families and society. However, the current situation reveals numerous external cultural influences on the younger generation of Hindus, such as involvement in motorcycle gangs, drinking, and gambling. This study aims to address the following research Application Of Susila Teachings In The Hindu Family Environment In Btn Belega Housing, Blahbatuh District, Gianyar District. The findings of this study demonstrate that the use of association theory can elucidate the practices of Hindu family heads in instilling moral teachings to their family members at BTN Belega Housing, Blahbatuh, Gianyar Regency. These teachings primarily involve the instillation of Susila, which encompasses moral values such as Tri Kaya Parisudha, Tri hita karana, Karmaphala, and Tat twam asi. Furthermore, the use of conditioning learning theory sheds light on the factors that influence Hindu family heads in imparting moral teachings to their family members at BTN Belega Housing, Blahbatuh, Gianyar Regency. The conditioning learning theory also elucidates the implications of instilling moral teachings by Hindu family heads on children at BTN Belega Housing, Blahbatuh, Gianyar Regency.